REPETITION AS A POWER OF DIFFERENCE IN CONTEMPORARY ART - Massoli, Emerson da Silva (Seven Editora, 2024)
The article presents conceptions of the terms Repetition and Difference, based on Gilles Deleuze (2018), addressing a general notion of Repetition, succeeding issues related to Difference; as well as discusses the three temporalities in the act of repeating, producing relationships with the conceptualizations of Contemporary Art by Alain Badiou (2013); thus, weaving links with the poetics that I develop, pointing out how repetition, seen as an artistic process, enhances the difference in Contemporary Art. DOI:https://doi.org/10.56238/sevened2024.037-051